Safety process capable of reducing explosion in hot disintegrating explosion of steel slag - JIANG XINPING; DAI DAKUI; YE XIAODONG; ZHU QINGSONG; WANG HONGLIN; LIANG JUN; DUAN JIANYONG; ZHAO CHUNHUI; LU HONGZU; YU HAIMING; LV ZHIGANG; WANG RUILI; et al. (2013)
The invention provides a safety process capable of reducing hot disintegrating explosion of steel slag. The process comprises a first step of controlling main chemical components of liquid steel slag as follows by mass: 30-55% of CaO, 9-22% of SiO2, 0.5-5% of Al2O3, 14-26% of TFe, 6-14% of MgO, 0.6-2% of MnO and 0.4-0.81 of P2O5; a second step of loading 202-315 kg of coke powder in an empty slag tank in advance, wherein the particle size of the coke powder is smaller than 1mm, and the carbon content of the coke powder is 75%; a third step of slowly adding the liquid steel slag of the first step into the empty slag tank, wherein the temperature of the liquid steel slag is 1,580 +/-20 DEG C, an adding amount is 9-14 tons and the liquid steel slag is completely added in 15 min; and a fourth step of excavating iron-containing materials solidified at the bottom of the slag tank by an excavator when the reaction is finished, wherein the residual steel slag is subjected to hot disintegration treatment according a n